Latino Attitudes Toward Ballot Propositions That Target Immigrants. (November 2016) - Stringer, Amy
In response to an increase in undocumented immigrants in the United States, several states have proposed and passed ballot measures that are intended to target immigrants, particularly Latinos. Yet, previous research has often failed to focus on Latino viewpoints in relation to these measures and the restrictions therein. As such, I utilize the 2006 Latino National Survey to examine how different sectors of the U.S. Latino population view policies that have been the focus of ballot initiatives targeting immigrants. I first make the distinction between native-born and foreign-born Latinos to determine whether opinions concerning proposed restrictions on immigrants differ between these groups. Furthermore, I examine whether foreign-born Latinos who are more assimilated into U.S. society differ in their attitudes on these measures than more recent immigrants. Results indicate a clear distinction with U.S.-born Latinos exhibiting more nativist views toward immigrants and restrictive measures than foreign-born Latinos.